IN VIVO BIOACCESSIBILTY AND BIODISTRIBUTION ANALYSIS OF HEAVY METALS IN LETTUCE OBTAINED FROM IRRIGATED DUMPSITES IN MUBI NORTH, ADAMAWA STATE. NIGERIA - Yamta, Shinggu Danbaki; Ibrahim, Bwatanglang Birma; Chindapi, Hyelnasinyi; Ujewe, David Jonathan (FUDMA JOURNAL OF SCIENCES, 2026)
The cultivation and consumption of vegetables (mainly lettuce) from farm-land in Mubi environs is of major public health concern. This study was performed to assess the bioaccessibility and biodistribution analysis of some heavy metals in lettuce obtained from the three different irrigated dumpsites (Wuro-Alkali, Wuro-Gude and Mayanka). Using in vivo based method, a total of 15 rabbits were used and were randomly assigned to cages with five rabbits per cage. The rabbits were fed with lettuce harvested from the irrigated farm-lands for this experiment. The lungs, kidney and liver of the experimental animals were harvested and analyzed for cadmium (Cd), zinc (Zn), Iron (Fe), magnesium (Mg), chromium (Cr), manganese (Mn), lead (Pb) and copper (Cu) using Atomic Absorption Spectrophotometer (AAS).The values of Fe and Cr in kidney of Wuro-Alkali, Wuro-Gude and Mayanka are above the control values of Fe 3.63±0.04 mg/kg and Cr 0.07±0.01 mg/kg. Similarly, the value of Cr in lungs at the three dumpsites are below the control value of 0.16±0.01 mg/kg. Also, the value of Fe and Cr in liver at the three dumpsites are above the control value of Fe 0.71±0.03 mg/kg and the value of Cr in lungs at the three dumpsites are below the control value of 0.03±0.01 mg/kg. Heavy metals concentration in these dumpsites may not appear to pose very serious environmental problems at the moment. However, accumulation of these metals after several years may pose a threat to human health and the environment.